INOVASI METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ummu Kalsum Yunus; Munira munira (IAIN Bone, 2021)
AbstractThis research was conducted to provide innovatation in learning techniques for the students. Innovative learning can be done with singing method to make it easier for the students to remember. This type of research is pre-experimental design with one group pre-test and post-test. The use of the singing method in Islamic education learning has a positive effect on improving memory skills, this can be seen from result of the hypothesis using the t-test (paired sample t-test) with SPSS version 23. Thus, according to the results obtained, it can be cocluded that the use of singing method is effectively for the students’ memory skills.Keywords: singing method, Islamic education, learning